Otantik liderlik ölçeği: Bir ölçek geliştirme çalışması - ÇETİN, MÜNEVVER (My University, 2023)
This study was carried out to develop a valid and reliable measuring tool specific to Turkish culture for determining the authentic leadership levels of school administrators. The research was carried out in 2020-2021 academic years with the participation of teachers who worked in the public primary schools, secondary schools and high schools in Istanbul. Based on the information obtained from the literature screening, the item pool of the draft scale was created. Scope validity analysis was performed using Lawshe technique. After the scope validity analysis, depending on the expert opinions, the item pool was reduced to 30 items. Exploratory factor analysis was carried out with data from 392 teachers. The total variance explained by the scale was determined to be 70.60%. The factor loadings of the items varied from 0.50 to 0.83. Seven Items were removed because they had loadings under multiple factors or had loading below 0.10. The scale was determined to have a 3-factor-structure with 23 items. There were 8 items in the factor of self-awareness, 5 items in the factor of transparency, and 10 items in the factor of decision making and morality. Pearson Product moment Correlation analysis was conducted to determine if there was a meaningful relationship between the exploratory factor analysis and those factors identified. Data from 389 teachers were included in the confirmatory factor analysis In order to check reliability of the scale Cronbach’s Alpha coefficient and Omega was calculated. Also Two Half-Tests (Spearman Brown) and the comparison of the items in the lower and upper 27% groups with the t-test were evaluated. All the analyses were carried out using SPSS 26 and AMOS software. The research results showed that \"Authentic Leadership Scale (ALS)\" was a valid and reliable measurement tool that has three factors, and could be used especially in leadership studies in educational organizations.

Bu çalışma okul yöneticilerinin otantik liderlik düzeylerini belirlemeye yönelik, Türk kültürüne özgü olan geçerli ve güvenilir bir ölçme aracı geliştirmek amacıyla gerçekleştirilmiştir. Araştırmanın evrenini 2020-2021 eğitim öğretim yılında İstanbul ilindeki resmî ilkokul, ortaokul ve liselerde görev yapmakta olan öğretmenler oluşturmaktadır. Literatür taramasından elde edilen bilgilere dayanarak, taslak ölçeğin madde havuzu oluşturulmuştur. Lawshe tekniği kullanılarak kapsam geçerlik analizi yapılmıştır. Kapsam geçerlik analizi sonrasında ölçek 30 madde olarak belirlenmiştir. 392 öğretmene ait verilerle açımlayıcı faktör analizi yapılmıştır. Ölçeğin açıkladığı toplam varyans % 70.60 olarak tespit edilmiştir. Maddelerin faktör yüklerinin 0.50 ile 0.83 arasında olduğu bulunmuştur. Yapılan analizlerde 7 madde binişik madde olduğu için ölçekten çıkarılmıştır. Açımlayıcı faktör analizi sonucunda, ölçeğin 3 faktörlü olduğu ve 23 maddeden oluştuğu belirlenmiştir. Ölçeğin öz farkındalık boyutunda 8 madde, şeffaflık boyutunda 5 madde ve karar alma ve ahlak boyutunda ise 10 madde bulunmaktadır. Açımlayıcı faktör analizi ile belirlenen bu faktörler arasında anlamlı bir ilişki bulunup bulunmadığını belirlemek amacıyla Pearson Çarpım Moment Korelasyon analizi yapılmıştır. 389 öğretmenden oluşan farklı bir örneklem grubu ile doğrulayıcı faktör analizi yapılmıştır. Doğrulayıcı faktör analizi de üç faktörlü yapıyı doğrulamaktadır. Güvenirlik açısından ise Cronbach Alfa katsayısı, Omega, madde toplam korelasyonları, İki Yarı Test (Spearman Brown) ve maddelerin alt ve üst %27’lik gruplarda t-testi ile karşılaştırılması yapılmıştır. Bu analizler için SPSS 26 ve AMOS programları kullanılmıştır. Araştırma sonuçları, Otantik Liderlik Ölçeği’nin eğitim örgütlerindeki liderlik çalışmalarında kullanılabilecek geçerli ve güvenilir bir ölçme aracı olduğunu göstermektedir.
Authentic leadership scale: A scale development study
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; authentic leadership; educational organizations; leadership; scale development; liderlik; eğitim örgütleri; otantik liderlik; ölçek geliştirme; leadership; educational organizations; authentic leadership; scale development